THE SPECIFIC EFFECTIVNESS OF STORYTELLING ON VOCABULARY RETENTION IN PARTICULAR AGE GROUP (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
Storytelling has long been recognized as a powerful pedagogical tool, particularly in language education, where meaningful context plays a crucial role in vocabulary acquisition and retention. This article explores the specific effectiveness of storytelling in enhancing vocabulary retention among a particular age group, with a primary focus on young learners aged 7–10 years. The study is grounded in cognitive and educational theories that emphasize the role of narrative structure, emotional engagement, and contextualized input in long-term memory formation. Vocabulary retention is examined not merely as the ability to recall isolated lexical items, but as the capacity to understand, use, and transfer newly acquired words in communicative situations.The article analyzes how storytelling supports vocabulary learning by activating learners’ prior knowledge, fostering deeper semantic processing, and increasing motivation and attention. Special attention is given to age-related cognitive characteristics, such as developing working memory, imagination, and linguistic sensitivity, which make storytelling particularly effective for this group. Through a critical review of existing empirical studies and classroom-based observations, the paper demonstrates that storytelling significantly improves both short-term and long-term vocabulary retention when compared to traditional memorization-based methods.Furthermore, the article highlights the importance of story selection, repetition, multimodal support, and learner interaction in maximizing vocabulary learning outcomes. The findings suggest that storytelling not only facilitates vocabulary retention but also contributes to learners’ overall language development, including listening comprehension, speaking fluency, and creative thinking. The study concludes that integrating storytelling into vocabulary instruction is a pedagogically sound and age-appropriate strategy that aligns with contemporary learner-centered approaches. The implications of this research are particularly relevant for language teachers, curriculum designers, and researchers seeking effective methods to enhance vocabulary retention in young learners.